Virtual Learning Program in the Midst of Covid19 Outbreak: EFL Learners' Perceptions - Meiga Ratih Tirtanawati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
The COVID-19 pandemic has become a worldwide medical problem and has majorly affected education. Thus, half way through the indeed semester of the scholastic year 2019/2020, learning strategies were conveyed through online learning. This new condition where right now the instructors and understudies are grappling with the thought, advancement, critical thinking aptitudes to usage and adjustment. Google classrooom and google meet as virtual learning platform are broadly utilized by instructors in educating and learning. Therefore, this study focused on exploring information related to undergraduate students’ perspective of virtual learning program amidst covid19 break. The implementation of the research is approximately three months using online questionnaires and interview to be used as data collection. The study involved 50 students of English Department at IKIP PGRI Bojonegoro. The data obtained showed that the majority of participants considered the use of Google classroom and google meet and Application in teaching and learning is effective and efficient virtual learning program. It also indicates that one of the constructive outcomes of virtual learning program activities is that such activities could fabricate students' innovativeness. Moreover, it shows that the pandemic circumstance was not a boundary to contributing emphatically to society. In addition, the obstacles were slow-speed internet access and students’ facilities during virtual learning.